Transition metal oxides: a new frontier in spintronics driven by novel quantum states and efficient charge-spin interconversion - Han, Yamin; Lao, Bin; Zheng, Xuan; Li, Sheng; Li, Run-Wei; Wang, Zhiming (Frontiers in Materials, 2024)
Transition metal oxides (TMOs) have emerged as promising candidates for spintronic applications due to their unique electronic properties and novel quantum states. The intricate interplay between strong spin-orbit coupling and electronic correlations in TMOs gives rise to distinct spin and orbital textures, leading to enhanced spin-momentum locking and efficient charge-spin interconversion. Remarkably, recent researches have unveiled the significant and highly tunable nature of charge-spin interconversion efficiency in TMOs, which can be manipulated through strategies such as electric field gating, epitaxial strain, and heterostructure engineering. This review provides a comprehensive overview of the recent advances in understanding the electronic band structures of TMOs and their correlation with charge-spin interconversion mechanisms. We summarize the tunability of these properties through various experimental approaches and discuss the potential implications for spintronic device applications. The insights gained from this review can guide future research efforts towards the development of high-performance, energy-efficient spintronic devices based on TMOs.